2021
DOI: 10.29303/jppipa.v7i4.819
|View full text |Cite
|
Sign up to set email alerts
|

Application of Project-Based Learning Through a STEM Approach to Improve Learning Outcomes During a Pandemic

Abstract: Research has been conducted on applying project-based learning (PjBL) through the Science, Technology, Engineering, and Mathematics (STEM) approach during the pandemic. Tests were given to 30 first-year students conducted by Distance Learning (DL). The research method used a pre-post experimental one-group design. The results showed a minimum pretest score of 50 and a maximum value of 70. After being treated, the minimum posttest result was 75, and the maximum result was 90. There was a significant difference … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 13 publications
1
12
0
Order By: Relevance
“…We included two studies in our corpus not involving PST as additional research that indicates STEM education in Indonesia is emerging for non-PST students. Asri et al (2021) 2022) only mentioned HEI locations, but, given that the author's affiliation comes from these locations, it was also inferred that the participants come from the authors' institutions. Hence, we identified 31 HEI from 15 provinces across Indonesia involved in STEM education research, as shown in Figure 5.…”
Section: Participant(s)' Discipline Backgroundmentioning
confidence: 99%
See 4 more Smart Citations
“…We included two studies in our corpus not involving PST as additional research that indicates STEM education in Indonesia is emerging for non-PST students. Asri et al (2021) 2022) only mentioned HEI locations, but, given that the author's affiliation comes from these locations, it was also inferred that the participants come from the authors' institutions. Hence, we identified 31 HEI from 15 provinces across Indonesia involved in STEM education research, as shown in Figure 5.…”
Section: Participant(s)' Discipline Backgroundmentioning
confidence: 99%
“…PSTs had increased science literacy skills (Amiruddin et al, 2021) and STEM content knowledge, particularly science content knowledge, followed by engineering, technology and mathematics content knowledge (Mayasari et al, 2019). The project-based learning STEM approach has promising implications for PSTs to create projects as teaching materials (Djulia & Simatupang, 2021) and improve learning outcomes, even if conducted in an online learning setting (Asri et al, 2021). Other articles show STEM improves problem-solving skills of PSTs (Wildani & Budiyono, 2022) and develops logical reasoning skills (Utomo et al, 2020).…”
Section: Stem Interventionmentioning
confidence: 99%
See 3 more Smart Citations